Revealing informal food flows through free Wi-Fi: Layer 3: Revealing food flows using registration forms. - Pham, Huong; Abbink, Henry; Huynh, Tuyen; Trung, Hieu; Nguyen, Thang; Lundy, Mark M. (2021)
In Vietnam, wholesale and retail traditional wet markets play an important role in food marketing systems.The in-person survey was conducted among vegetable, pork and rice sellers using registration forms in 5 traditional wet markets in Hanoi, Vietnam in order to partially characterize the food flow of different actors as well as to understandphysical and social characters for different foods in the flow as well as strengths and constraints in the food distribution system. The survey is one of 3 layers for data collection under the project “Revealing informal food flows through free Wi-Fi”. Food quantity in the different traditional markets, Mapping the flow of food and food-related actors in wholesale and retail traditional markets, Food loss in the traditional markets and The strengths and challenges of the food flows that network actors face.